Secondary Metabolite Changes in Tedara (Bituminaria bituminosa L.) Genotypes in Different Growing Period - Erdem Gülümser; Sema Leblebici; Zeki Acar; İlknur Ayan; Cihan Darcan (Journal of Agricultural Sciences)
In this study, secondary metabolite amounts of leaf samples belonging to 12 different Bituminaria bituminosa (L.) C.H. Stirtion genotypes were determined at the beginning of growth, budding and at the beginning of flowering periods. Leaf samples belonging to B. bituminosa genotypes were dried under natural conditions and extracted using a microwave system (NEOS). Furanocumarins (psoralen and angelicin), isoflavonoids (daidzein, genistein) and isoflovan glycosides (daidzin and genistin) obtained by LC-MS / MS. While the secondary metabolite contents determined in B. bituminosa differed among growth periods, genotype difference was found to be more effective on these metabolite contents. As a result, all genotypes performed remarkably in terms of secondary metabolites. Besides, the number 12 genotype (Samsun-Kavak) was prominent in terms of angelicin, daidzein, genistein, daidzin, and genistin compared to the other genotypes.